Karakteristik Kimia dan Organoleptik Biskuit dengan Penambahan Tepung Kacang Kedelai (Glycine max) dan Tepung Kulit Buah Naga Merah (Hylocereus costaricensis) - Dian Puspita; Noor Harini; Sri Winarsih (Universitas Muhammadiyah Malang, 2021)
Indonesia is a country that has a high level of biscuit consumption. This is supported by many local food commodities. Therefore, many food products have emerged that use local food ingredients, such as bread, biscuits and cakes. One effort that can be made to enrich the nutritional content of biscuits is to add soybean flour which is rich in protein and flour of red dragon fruit peel which is rich in dietary fiber. The purpose of this study was to determine the effect of the ratio of wheat flour, soybean flour and red dragon fruit peel flour to chemical and organoleptic quality of biscuits. This research used a simple randomized block design with ratio of wheat flour, soybean flour, and red dragon fruit peel flour consisting of 10 levels: P0 (100%:0%:0%), P1 (80%:10%:10%), P2 (70%:20%:10%), P3 (60%:30%:10%), P4 (75%:10%:15%), P5 (65%:20%:15%), P6 (55%:30%:15%), P7 (70%:10%:20%), P8 (60%:20%:20%), P9 (50%:30%:20%). Each level is repeated 2 times. The parameters being observed were level of protein, fat, crude fiber, water, ash, and organoleptics (aroma, taste and texture). The results showed that the proportion of wheat flour, soybean flour and red dragon fruit peel flour had a very significant effect on level of water, protein, crude fiber, and organoleptic (taste, aroma, and texture). Treatment of biscuits with proportion of wheat flour 60%: 30% soybean flour: 10% red dragon fruit peel flour was the best treatment with level of water 6,58%, ash 0,76%, fat 27,95%, protein 9,74%, crude fiber 6,10%, organoleptic of taste 4,65 (delicious), aroma (rather tasty), and texture (rather not hard)